1977
DOI: 10.9749/jin.58.103
|View full text |Cite
|
Sign up to set email alerts
|

On the Separation of Traffic at Straight Waterway by Distribution Model of Ship's Paths

Abstract: Author proposed a method for determining the breadth of buffer zone Qn the separated tra班 c lanes for var 三 〇 us width of waterway and traMc volumes . The method was based on the distribution mQdd of ship ' s paths derived frQm the statistical analysis of the Radal photographs at narrow channels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As a result, it was analyzed that the ship passing through the approach area of Busan Port had a passage that deviated in the direction of the breakwater, and as it approached the breakwater, and the standard deviation was also analyzed to decrease. Inoue (1977) demonstrated that the traffic probability distribution in the fairway is a normal distribution. However, as a result of the passage pattern analysis according to the marine traffic analysis, the passage pattern was analyzed to be different from the general passage pattern when passing near the breakwater.…”
Section: Gateline Analysismentioning
confidence: 99%
“…As a result, it was analyzed that the ship passing through the approach area of Busan Port had a passage that deviated in the direction of the breakwater, and as it approached the breakwater, and the standard deviation was also analyzed to decrease. Inoue (1977) demonstrated that the traffic probability distribution in the fairway is a normal distribution. However, as a result of the passage pattern analysis according to the marine traffic analysis, the passage pattern was analyzed to be different from the general passage pattern when passing near the breakwater.…”
Section: Gateline Analysismentioning
confidence: 99%
“…Many studies have been conducted on the traffic distribution and patterns in a port because these are important for understanding and analyzing the flow of ships. Inoue [35] demonstrated that the traffic distribution for 1-way or 2-way traffic is a normal distribution. Kim and Kwon [36] assumed a normal distribution in analyzing the collision probability of the Mokpo bridge and Incheon bridge.…”
Section: Normality Testmentioning
confidence: 99%
“…A ship can pass from the fairway's center to the right of the ship's bow direction. Considering these characteristics, the distance between the ship and bridge pier on the right side of the ship's bow side was measured and a normality test was conducted [35].…”
Section: Normality Testmentioning
confidence: 99%
“…(d ) gas tankers, (e) oil tankers, and, for both loaded and ballast conditions: Fujii et al [10] and Inoue [11], giving empirical expressions for the distribution parameters. More (d ) speed, recent radar observations have been published by (e) draught, Gluver and Olsen [12] and Randrup-Thomsen et al…”
Section: Notationmentioning
confidence: 99%
“…Fig 11. Horizontal force indentation as a result of a collision between a concrete bridge and a 10 m wide ship's deck house…”
mentioning
confidence: 99%